Change Factors Towards Sustainability at the Example of Hospitals’ Secondary Processes - Bustamante, Silke; Prüße, Heike; Pelzeter, Andrea; Ihlee, Franziska (European Journal of Sustainable Development, 2023)
Secondary processes in hospitals are causing a major part of hospitals’ carbon footprint. At the same time, initiating change towards sustainability is more difficult in secondary processes than in other processes: Often, they are not under the complete control of hospitals and involve other actors, such as service providers or purchasing companies. The current research aims to shed light on factors influencing change in secondary processes at the example of hospitals in Germany. Building on a framework that distinguishes change factors on a micro-, meso- and macro-level, it is analysed which aspects are positively or negatively influencing change towards more sustainability. To this end, qualitative interviews with eleven experts from hospitals and service providers have been conducted and results have been assigned to the three levels of change. Results underline the importance of inter-organisational collaboration and the design of structures and processes to establish regular cooperation and coordination. They also show that business relationships between hospitals and service providers are rather cost-related than transformational. Sustainability offers the opportunity to modify existing roles and develop future-proof businesses. The paper contributes to existing research by focusing on multi-organisational perspectives. On a practical level, it supports hospitals in designing their change strategies and processes jointly and in collaboration with other parties that are part of secondary processes. Keywords: sustainable change, (inter-) organisational change, hospitals’ secondary processes